The Sensitivity of Southern Ocean Air-Sea Carbon Fluxes to Background Turbulent Diapycnal Mixing Variability - Elizabeth Ellison; Ali Mashayek; Matthew Mazloff (Zenodo, 2023)
The mixing map for background diapycnal diffusivity used in the paper 'The Sensitivity of Southern Ocean Air-Sea Carbon Fluxes to Background Turbulent Diapycnal Mixing Variability' in the spatially variable mixing case ExVar. The ExVar map is constructed as the sum of contributions from tidesand topographically-generated lee waves and features horizontal and vertical variations in a background mixing rate.